University freshman mentoring effectiveness and scale enhancement / Yenwan Chong and Lip-Sam Thi - Chong, Yenwan; Lip-Sam, Thi (Universiti Teknologi MARA, 2020)
Graduate unemployment has worsened following the global crisis caused by the coronavirus disease 2019 (COVID-19) and has created increased pressures on universities to enhance their graduates’ employability. Past studies have indicated that mentoring programs can positively impact student soft skills development and employability. While undergraduate mentoring programs have mushroomed, research on undergraduate mentoring has not kept pace. This study used a mixed methods approach to examine the effectiveness of a public university’s initiative in mentoring new undergraduates. Using the College Student Mentoring Scale (CSMS), this study found that the university’s undergraduate mentoring initiative is moderately effective. The CSMS assessed four mentoring dimensions, namely academic subject knowledge support, degree and career support, psychological and emotional support as well as role modelling. The results of this study highlighted the mentoring functions that are considered as least effective so that informed and targeted efforts can be undertaken to enhance university freshman mentoring. Findings from this study suggest that a new dimension namely mentor-mentee compatibility, competencies and expectations could be added to the College Student Mentoring Scale (CSMS) to enhance concept operationalization. A limitation of this study is that it is based on mentees’ perspectives only. Future research could include the perspectives of mentors as well.